Neurochemical basis for the photic control of circadian rhythms and seasonal reproductive cycles: role for acetylcholine. - Earnest, D J (1985)
A pharmacological approach was used to examine the role of acetylcholine in the photic control of circadian rhythms and seasonal reproductive cycles. The experimental protocol was designed to determine whether the administration of carbachol, a cholinergic agonist, could mimic the effects of brief light pulses on gonadal function and/or the circadian rhythm of wheel-running activity in golden hamsters. Intraventricular injections of carbachol, administered singularly at discrete phase points throughout the circadian cycle, induced phase-dependent shifts in the free-running rhythm of activity similar to those caused by a brief light exposure. Injections of carbachol once every 23.33 hr for 9 weeks entrained the activity rhythm and stimulated the neuroendocrine-gonadal axis in a manner similar to that observed after the presentation of 1-hr light pulses at this frequency. In contrast, the administration of carbachol once every 24 hr did not consistently provide an entraining signal for the activity rhythm and did not stimulate reproductive function. Importantly, the effects of carbachol on the seasonal reproductive response were correlated with the timing of the injections relative to the activity rhythm. These findings suggest that acetylcholine may play an important role in the mechanism by which light regulates circadian rhythms and seasonal reproductive cycles.